2021
DOI: 10.1029/2020ja028761
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Seismo‐Ionospheric Anomalies Possibly Associated With the 2019 Ridgecrest (California) Earthquakes by GNSS, CSES, and Swarm Observations

Abstract: The association between earthquakes and ionospheric precursors has been widely reported in previous studies. The Swarm satellite constellation, the China Seismo‐Electromagnetic Satellite (CSES), and the ground‐based global navigation satellite system (GNSS) observations provide us new opportunities to detect ionospheric precursors to earthquakes for a better understanding of the seismic‐ionospheric coupling. In California, two shallow earthquakes with magnitudes of 6.5 and 7.1, the two higher magnitude events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…[14] claimed a chain of processes compatible with a LAIC and characteristics of complex systems, like earthquakes. Furthermore, an increase of magnetic anomalies was detected by Swarm satellites about 220 days before the earthquake by Marchetti et al [15] and anomalies in Total Electron Content and CSES-01 Ne data about one week before the mainshock by Xie et al [16]. In addition, De Santis et al [14] identified an increase of electron density 33 days prior to the mainshock as unique in several months of data investigation from Point Arguello ionosonde (whose position is represented by the blue triangle in the map in Figure 3) and Swarm Alpha here reported in Figure 3.…”
Section: Resultsmentioning
confidence: 94%
“…[14] claimed a chain of processes compatible with a LAIC and characteristics of complex systems, like earthquakes. Furthermore, an increase of magnetic anomalies was detected by Swarm satellites about 220 days before the earthquake by Marchetti et al [15] and anomalies in Total Electron Content and CSES-01 Ne data about one week before the mainshock by Xie et al [16]. In addition, De Santis et al [14] identified an increase of electron density 33 days prior to the mainshock as unique in several months of data investigation from Point Arguello ionosonde (whose position is represented by the blue triangle in the map in Figure 3) and Swarm Alpha here reported in Figure 3.…”
Section: Resultsmentioning
confidence: 94%
“…To verify LAIC, abnormal variations of TEC and electron density are detected. Previous studies show that the enhancement of TEC related to earthquake is more prominent over the earthquake breeding zones (Shah, Ahmed, et al., 2020; Shah & Jin, 2015; Xie et al., 2021). In addition, Xie et al.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, Xie et al. further reported that TEC anomalies were positively correlated with electron density anomalies (Xie et al., 2021). Therefore, in this study, the positive anomalies of TEC and electron density are extracted and used for subsequent analysis.…”
Section: Resultsmentioning
confidence: 98%
“…For the GIM data at 2 h intervals with a spatial resolution of 2.5 In order to analyze the anomalous changes of the GIM and GPS TECs around the epicenter, we extracted the abnormal signals via the sliding interquartile range method with a sliding background of 15 days [29,45]. The method determined a sliding window for every successive 15 days and separately computed the median (M) and the associated interquartile range (IQR) to construct the upper bound M + K × IQR and the lower bound M − K × IQR [33,37,38]. A positive anomaly was situated above the upper bound and a negative anomaly was situated below the lower bound.…”
Section: Tec Data and Methodsmentioning
confidence: 99%
“…Finally, seismic precursor signals propagate upward from the atmosphere to the ionosphere under certain conditions and cause the abnormal disturbances in the ionospheric multi-parameter, which is known as the seismo-ionospheric coupling effect [25][26][27][28]. A large number of EQ case studies revealed that due to the critical changes in crustal tectonics during the pre-seismic phase of major EQs, the ionospheric electron density (Ne), ion density, and other parameters in the vicinity of the EQ preparation zones may show different degrees of anomalous disturbances [29][30][31][32][33][34][35][36][37][38]. For instance, Liu et al [29] statistically analyzed EQs with a magnitude of 6.0 or above in Taiwan from 1994 to 1999 and found that the precursors appeared for 1-6 days in the form of an foF2 decline before these EQs.…”
Section: Introductionmentioning
confidence: 99%